Effects of a new continuous nursing program on the short-term and long-term low back pain in patients after UBED: a retrospective study based on 282 patients - Li, Jucai; Song, Yanli; Wu, Lumei; Su, Dan; Wang, Lin-Feng (Frontiers in Surgery, 2024)
Background: Unilateral biportal endoscopic discectomy (UBED) is a mainstream minimally invasive surgery for the treatment of lumbar degenerative diseases. However, some patients still have persistent low back pain (LBP) symptoms in the short and long term after surgery, which may be related to improper postoperative nursing and rehabilitation process of patients. Whether continuous nursing can improve the symptoms of patients after UBED needs to be studied. Methods: This study retrospectively enrolled 282 lumbar disc herniation (LDH) patients who underwent UBED in our hospital from January 2019 to January 2022. Patients were divided into two groups according to whether they accepted the continuous nursing program. There were 147 patients in the traditional nursing group and 135 patients in the continuous nursing group. Demographic characteristics, radiological parameters and follow-up data of the patients were collected. Finally, the risk factors of LBP after UBED were analyzed. Results: The visual analog scale (VAS) score of LBP in the continuous nursing group was 0.97 ± 1.159 at 3 rd month after operation, 0.61 ± 0.954 at 12 th month after operation, and VAS of legs pain was 0.23 ± 0.421 at 12 th month after operation, which were better than those in the traditional nursing group (1.51±1.313, 1.10 ±1.076, 0.68 ±0.788, p < 0.001) The ODI score of the continuous nursing group was lower than that of the traditional nursing group at 12 th month after operation (7.36 ±6.526 vs. 12.43 ± 6.942, p < 0.001). The rehabilitation completion score (7.98 ± 1.857), efficacy satisfaction score (9.13±1.101) and re-herniation worry score (1.97±1.217) in the continuous nursing group were better than the traditional nursing group (4.14±3.066, 8.28±1.240, 2.79±1.973, P < 0.001). The re-herniation rate within 1 year was similar between the two groups (3/135 vs. 2/147, p=0.673). No incision infection occurred. Multivariate regression analysis showed that risk factors for persistent LBP at 3-month follow-up were degenerative disc (OR: